2021
DOI: 10.3389/fchem.2021.666161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of NAP-XPS and Cryo-XPS for the Investigation of Surface Chemistry of the Bacterial Cell-Envelope

Abstract: Bacteria generally interact with the environment via processes involving their cell-envelope. Thus, techniques that may shed light on their surface chemistry are attractive tools for providing an understanding of bacterial interactions. One of these tools is Al Kα-excited photoelectron spectroscopy (XPS) with its estimated information depth of <10 nm. XPS-analyses of bacteria have been performed for several decades on freeze-dried specimens in order to be compatible with the vacuum in the analysis chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Recently, we have been applying a cryogenic approach to XPS (cryo-XPS) where a biological sample is fastfrozen to liquid nitrogen temperatures prior to analysis and maintained at this temperature throughout the analysis time (Ramstedt and Shchukarev, 2016;Shchukarev and Ramstedt, 2017). Data from cryo-XPS has been shown to be in close agreement with data obtained from near-ambient pressure XPS for a reference bacterial strain (Kjaervik et al, 2021). Furthermore, we developed a model to predict the composition of lipid, polysaccharide and peptide (protein and/ or peptidoglycan) at the surface of the cell from the C 1s spectrum ("the Umeå method").…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we have been applying a cryogenic approach to XPS (cryo-XPS) where a biological sample is fastfrozen to liquid nitrogen temperatures prior to analysis and maintained at this temperature throughout the analysis time (Ramstedt and Shchukarev, 2016;Shchukarev and Ramstedt, 2017). Data from cryo-XPS has been shown to be in close agreement with data obtained from near-ambient pressure XPS for a reference bacterial strain (Kjaervik et al, 2021). Furthermore, we developed a model to predict the composition of lipid, polysaccharide and peptide (protein and/ or peptidoglycan) at the surface of the cell from the C 1s spectrum ("the Umeå method").…”
Section: Introductionmentioning
confidence: 80%
“…81 In later studies of the bacterium Pseudomonas fluorescens , it has been shown that this difference can be minimised by using fast freezing in cryo-XPS. 83 Recently, the first NAP-XPS studies of radiation damage in fully hydrated double-strand DNA have been published. 84 DNA damage by ionising radiation is of fundamental importance to cancer therapy, but is difficult to study by XPS in realistic environments.…”
Section: In Situ Methods: Developments In Near-ambient Pressure Xpsmentioning
confidence: 99%
“…The cryo-XPS data set (n=9) reported good reproducibility between biological replicas with an average elemental composition +/-standard deviation of: 58.3 +/-1.7 at% C, 10.2 +/-1.0 at% N and 29.0 +/-1.6 at% O (Ref. 3). The variation in C components as ratio to total C were found to be 0.365 +/-0.011 at 285.0 eV, 0.419 +/-0.012 at 286.5 eV, 0.189 +/-0.012 at 288.1 eV and 0.026 +/-0.013 at 289.1 eV (Ref.…”
Section: Introductionmentioning
confidence: 95%
“…Recent work has shown that XPS spectra obtained from hydrated bacteria using near-ambient pressure XPS and cryo-XPS are comparable (Ref. 3). Furthermore, the compositional stability and reproducibility between cultures grown and subsequently analyzed using XPS in two different labs and locations led us to suggest that this strain could function as a reference sample for XPS analyses of Gramnegative bacterial cells (Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation